Upaya Menghilangkan Jenis Kecacatan Mulut Melipat dengan Tahapan DMAIC di PT X - Donny Gunawan (Jurnal Titra, 2021)
The research was conducted to eliminate the type of folding mouth defect in the production output at PT X. Folding mouth defect is the cause of leakage in the bottle. The problem is seen based on customer complaint data in 2020, namely 19% of customers complained about leaking bottles and the company has a target to achieve zero defects in products received by consumers. Efforts to eliminate the type of folding mouth defect are carried out using the Define, Measure, Analyze, Improve and Control (DMAIC) stages to analyze the root cause of the problem and provide a proposed improvement plan that will be carried out. Analysis of the causes of the problem is done using the help of fishbone diagrams. Four factors cause the problem of folding mouth defects, namely man, machine, method and material factors. One of the root causes of problems in folding mouth defects is a loose blowpin. Improvements that can be made to eliminate folding mouth defects are to carry out an overall audit of the machine and replace abnormal parts.